2019
DOI: 10.1038/s41598-019-48336-5
|View full text |Cite
|
Sign up to set email alerts
|

The undeveloped properties of GABA neurons in the ventral tegmental area promote energy intake for growth in juvenile rats

Abstract: Juvenile animals show higher energy intake (EI) per body weight (BW) to meet the energy requirements for growth. However, the underlying mechanisms that induce high EI/BW in juvenile animals remain unknown. The EI from a control diet (CD) and high fat diet (HFD), as well as BW changes were compared between juvenile (3 weeks old) and adult (8 weeks old) rats. BW gain and EI were increased in the HFD-fed adult rats compared to the CD-fed adult rats. However, in the juvenile rats, there were no differences in BW … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 40 publications
1
7
0
Order By: Relevance
“…As for the energy intake, the HFD adult group showed higher energy intake from the beginning of HFD feeding. This corresponds to the previous studies showing energy intake being significantly higher in HFD fed rats, compared NCD fed rats for the first five to 6 days and then decrease [7,15]. HFD is a highly palatable food and known to stimulate reward related area, such as ventral tegmental area (VTA) of the brain.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…As for the energy intake, the HFD adult group showed higher energy intake from the beginning of HFD feeding. This corresponds to the previous studies showing energy intake being significantly higher in HFD fed rats, compared NCD fed rats for the first five to 6 days and then decrease [7,15]. HFD is a highly palatable food and known to stimulate reward related area, such as ventral tegmental area (VTA) of the brain.…”
Section: Discussionsupporting
confidence: 89%
“…However, even with the same caloric intake, HFD is known to induce significantly higher BW increase compared to NCD in adult rats [23]. Our previous study revealed that HFD feeding increases locomotor activity via undeveloped properties of GABA neurons in VTA and decreases inhibitory input to dopamine neurons leading to hyperactivity of dopamine neurons in the VTA of juvenile rats [7]. Thus, fact that there were no differences in BW between HFD and NCD fed juvenile rats in the current study may be explained by increasing energy expenditure following increased locomotor activity.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations